Effect of Toxoplasma gondii Infection on the Level of Luteinizing and Follicle Stimulating Hormones in Women with Polycystic Ovary Syndrome - Muna Jalal Aziz; Abeer Abbas Ali; Mohammed Fadhil Hameed; Basima Ahmed Abdullah (Medical Journal of Babylon)
Background: The protozoan parasite Toxoplasma gondii is responsible for the most significant zoonotic illness in the world, Toxoplasmosis. It is possible for T. gondii to be transferred transplacentally from the mother to the fetus if it is contracted during pregnancy and causes abortion or congenital deformity. Objective: To investigate the correlation between polycystic ovarian syndrome and toxoplasmosis, as well as to examine certain related sex hormones, luteinizing hormone (LH) and follicle stimulating hormone (FSH). Materials and Methods: The current study was conducted at Kirkuk General Hospital and Gynaecological and Pediatric Hospital in Kirkuk city, Iraq, between November 1, 2022 and March 21, 2023. The study included 200 blood samples collected from women who had abortions. The serum used to measure levels of LH and FSH. Results: Out of the 200 aborted women, only 40 (20%) of them were PCO positive (poly cystic ovarian syndrome). The 40 positive PCO subjects were divided into four groups according to the presence of T. gondii antibodies: PCO +ve and Toxo IgM +ve (7.5%), PCO +ve and Toxo IgG +ve (15%), PCO +ve and Toxo IgM ‐ve (42.5%), PCO +ve and Toxo IgG ‐ve (35%). Conclusion: There were significant differences in the FSH and LH level in the study groups. The level of LH in four groups the highest mean was in Toxo IgM and PCO +ve (9.190 ± 3.710) with P value 0.046. In the level of FSH in four groups the highest mean was in Toxo IgG +ve and PCO +ve (8.776 ± 2.061) and the lowest mean was in Toxo IgM +ve and PCO +ve (5.790 ± 3.25) with a P value of 0.045.